Enhanced hydrogen sorption properties of uniformly dispersed Pd-decorated three-dimensional (3D) Mg@Pd architecture - Lu C.; Panda S.; Zhu W.; Ma Y.; Zou J. (My University, 2025)
This study demonstrates the hydrogen sorption improvement of Mg through the three-dimensional decoration of a noble catalyst. An Mg@Pd composite was synthesized by decorating Pd nanoparticles onto the Mg matrix via a facile solid-gas reduction method. Electron tomography analysis confirms the formation of a three-dimensional (3D) architecture of the Mg@Pd particulate composite. The Mg@Pd composite shows excellent hydrogenation/dehydrogenation kinetics even at low temperatures as compared to a catalyst-free Mg sample. Moreover, the hydrogenated Mg@Pd composite can desorb hydrogen at as low as 246 °C that is 87 °C lower than that of the pure MgH2. Hydrogenation of the Mg@Pd composite leads to the development of a multiphase system consisted of PdH0.706, MgPd and MgH2 whereas dehydrogenation occurred via two simultaneous desorption reactions results in Mg6Pd and Mg phases. The uniform dispersion of Pd nanoparticles on the surface of the 3D Mg matrix has provided with fast catalytic interfaces via the hydrogen “spillover” mechanism while the concomitant hydrogen diffusion processes are enhanced by the “hydrogen pump” effect of PdH0.706/MgPd interfaces. Furthermore, the low temperature hydrogen sorption performances of the Mg@Pd composite can be attributed to the interphase reversibility between MgPd and Mg6Pd leading to the thermodynamic destabilization of MgH2. This study suggests that strategically new approaches can govern significant improvements in hydrogen storage properties of Mg-based systems. © 2023 Hydrogen Energy Publications LLC